The Correlation of Gene Expression of Inflammasome Indicators and Impaired Fertility in Rat Model of Spinal Cord Injury: A Time Course Study - Nikmehr, Banafsheh; Bazrafkan, Mahshid; Hassanzadeh, Gholamreza; Shahverdi, Abdolhossein; Sadighi Gilani, Mohammad Ali; Kiani, Sahar; Mokhtari, Tahmineh; Abolhassani, Farid (Urology Journal, 2017)
Purpose: Expression assessment of the inflammasome genes in the acute and the chronic phases of Spinal cord injury (SCI) on adult rat testis and examination of associations between inflammasome complex expression and sperm parameters. Materials and methods: In this study, 25 adult male rats were randomly divided into 5 groups. SCI surgery was performed at T10-T11 level of rats’ spinal cord in four groups (SCI1, SCI3, SCI7, and SCI56). They were sacrificed after 1day, 3days, 7days and 56 days post SCI, respectively. One group remained intact as control (Co). CASA analysis of sperm parameters and qRT-PCR (ASC and Caspase-1) were made in all cases. Results: Our data showed a severe reduction in sperm count and motility, especially on day 3 and 7. ASC gene expression had a non-significant increase on day 1 and 56 after surgery compared to control group. Caspase-1 expression increased significantly on day 3 post injury versus the control group (P = .009). Moreover, Caspase-1 overexpression, had significant correlations with sperm count (r = -0.555, P = .01) and sperm progressive motility (r = -0.524, P = .02). Conclusion: Inflammasome complex expression increase following SCI induction. This overexpression correlates to low sperm parameters in SCI rats.